The Song of Songs and the Testament of Solomon: Solomon's Love Poetry and Christian Magic - Rainbow, Jesse (Harvard theological review, 2007)
A widespread early Christian tradition regarded Solomon as the great exorcist and magician of antiquity, the forerunner of the exorcistic activity of Jesus, and the genius of later Christian magic and divination. In time, this tradition (henceforth the “Solomon magus” tradition) would become increasingly syncretistic and would yield the numerous grimoires and claviculae of the Middle Ages, but in the early centuries of Christianity, the tradition produced texts which were more or less haggadic, that is, engaged in the exegesis of canonical materials and rooted in earlier Jewish interpretive traditions. Modern students of the documents of this tradition have long perceived its debt to the Old Testament, particularly to the portrait of Solomon in 1 Kgs 5:9–14 (4:29–34), a text which both traditional Christian and modern critical interpreters have subsequently explained in nonmagical terms. While Solomon's magical identity is widely recognized to be inspired by the biblical description of his greatness, little is known about how readers in the Solomon magus tradition interpreted the canonical books of traditional Solomonic authorship—the Song of Songs, Proverbs, Ecclesiastes and the Wisdom of Solomon.